Prinsip Kelakar Sebagai Strategi Perekat Komunikasidalam Wacana Indonesia Lawak Klub (ILK) TRANS TVdan Implikasinya Sebagai Bahan Ajar di SMA - Noor, Khilyatin Ulin, Prof. Dr. Harun Joko Prayitno, M.Hum, Prof. Dr. Markhamah, M.Hum (2016)
The purpose of this study, there are three. (1) Identify the embodiment follow the principle of discourse ILK joke. (2) Describe the level of civility in discourse ILK principle joke. (3) Describe the use of the principle of banter in the discourse of ILK as a communication strategy in the adhesive material of learning conversational skills in high school. This type of research is qualitative descriptive study. The data in this study of the speech containing the follow prank in wacan ILK. Data collection techniques in this study using techniques of documentation and recording technique. Sources of data in this study was footage ILK-run for 10 episodes. Methods of data analysis in this study is a content analysis techniques to analyze footage of the event Indonesia Lawak Klub form of discourse dialog containing the principle joke. In addition the data analysis techniques are heuristic analysis techniques. Presentation of the results of data analysis techniques in this study using an informal presentation. The results of this study there are three. (1) The form of speech acts jokes used in the discourse of ILK was found five forms TT ie TT assertive, directive TT, TT expressive, commissive TT and TT declarative. TTA (Speech Acts Aserif) include states, demanding, admits, pointing, report, testify, and mentions. While TTD (Speech Acts Directives) covers, asking force, suggest, tell. Then for TTE (Expressive Speech Acts) covers flatter, praise, blame, criticize. For TTK (Speech Acts commissive) only found threatening. And for TTDE (Speech Acts Declarative) includes impressive and classify. (2) Politeness Levels are polite speech on wisdom maxims, maxims simplicity, and maxims agreement. Speech is not polite deviations wisdom maxims maxims, maxims simplicity, generosity irregularities maxims, maxims award, agreement maxim and maxim kesimpatian irregularities. (3) Implementation of use of the principle of banter as the glue of communication strategies can be used for learning conversational skills in the Junior High School (SMP) / (MTs) and High School (SMA) / (MA), instructional media modeling and evaluation process in the form of speech acts ,